Effect of Pranayama on Breath Holding Time of College Students - Patel, Shri Krishna; Srivastava, Sanjay (Integrated Journal for Research in Arts and Humanities, 2024)
Context: Pranayama is a method for regulating and manipulating breath and meditation. It enables individuals to achieve a state of profound relaxation while maintaining mental alertness. Recent research on the effects of yoga on the respiratory system over the long term has shown promising results. Aim: This study's primary objective was to assess pranayama's impact on breath holding time. Settings and Design The present investigation entail the examination of a group of 25 male participants who exhibited good health and fell within the age range of 21 to 26 years. Methods and Material: The participants who met the specified inclusion and exclusion criteria were subjected to a 15-minute pranayama session facilitated by a yoga instructor over a period of 12 weeks. Respiratory functioning before and after yoga was assessed using measurements of breath-holding duration. The parameters were analyzed using the student t-test. Results: The breath-holding duration have shown a notable increase compared to the period before engaging in yoga practice. Conclusions: The findings of this study demonstrate the positive impacts of consistent engagement in pranayama on respiratory functioning.